Childhood, Futurity, and Settler Time - Stirling, Bridget (Journal of Childhood Studies)

(untitled) (Canadian Association for Young Children, 2022)
Settler childhood’s futurity is grounded in settler time: the colonial temporal structures of settlers that view time as strictly delineated, in opposition to Indigenous temporal heterogeneity—the coexistence of a multiplicity of temporalities. Mark Rifkin describes this temporal heterogeneity as having the power to unsettle settler frames of reference. In response to Adam Gaudry’s call for settlers to engage in insurgent research by engaging with Indigenous research and worldviews while focusing on settler problems, turning to the tension of settler time with Indigenous temporal sovereignty alongside Barbara Adam’s conception of temporal care relations offers a way to unsettle settler childhoods. Bringing together two ways of rethinking temporality through Dwayne Donald’s conception of ethical relationality enables a critique of colonialism without seeking to take up Indigenous childhoods to fill the broken spaces in settlers’ own. This effort reflects Alexis Shotwell’s warning to attendees of the Common Worlds colloquium Responding to Ecological Challenges with/in Contemporary Childhoods: An Interdisciplinary Colloquium on Climate Pedagogies to be attentive to epistemic extractivism and the problem of settlers seeking to resolve the damage of colonialism through seeking to behave as if they are Indigenous. Instead, I propose a way forward in which children are reentangled in both common worlds and common fates.